The Balance of N, P, and Manure Fertilizer Dosage on Growth and Yield of Peanuts in Alfisols Dryland - Suryono Suryono; Hery Widijanto; Eka Miftakhul Jannah (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
Peanuts cultivation in alfisols dryland limited by low levels of soil fertility. An agricultural intensification that could be done is application of organic and inorganic fertilizer. This research aimed to study the balance of N, P, and manure fertilizer dosage on growth and yield of peanuts in alfisols dryland. The research was done in April 2014 - September 2014 in Sukosari, Jumantono, Karanganyar. This research was compiled using a Randomized Completely Block Design (RCBD) factorial with three factors, there are dose of urea, SP-36 and cow manure fertilizer. The results showed that the dose combinations of urea, SP-36, and cow manure fertilizer have no interaction affected all of variable plant. The application of 300 kg ha-1 SP-36 fertilizer increased the number of pods and weight of pods, while the weight of 1000 seeds was improved by application of 150 kg ha-1 urea fertilizer.